Use of bag-mask ventilation for cardiopulmonary resuscitation: Do we need more evidence for low resource setting? - Rijal, Suraj (Journal of General Practice and Emergency Medicine of Nepal, 2018)
Clinical Question: Can victims of cardiac arrest be managed without endotracheal intubation in resource-limited settings without compromising survival with good neurologic outcomes? Article Chosen: Jabre P, Penaloza A, Pinero D, et al. Effect of Bag-Mask Ventilation versus Endotracheal Intubation During Cardiopulmonary Resuscitation on Neurological Outcome After Out-of-Hospital Cardiorespiratory Arrest: A Randomized Clinical Trial. JAMA. 2018;319(8):779-787. doi:10.1001/jama.2018.0156Objective: To assess the non-inferiority of bag-mask valve ventilation versus endotracheal intubation for advanced airway management with regard to survival with favorable neurological outcome at 28 days.Conclusion: Among several take away from this paper, our conclusion is why not to continue bag and mask ventilation if working well instead of switching to endotracheal intubation while doing cardiopulmonary resuscitation in a cardiac arrest patient.